PENERAPAN FREEWARE GOOGLE-SHEET UNTUK CEK LIS PERSEDIAAN BARANG DAGANGAN PADA USAHA KECIL & MENENGAH - Wahyudi, Hijrah; Mardiyati, Mardiyati (STIE 'INDONESIA' Pontianak, 2025)
This study aims to examine the use of Google Sheets, a free and cloud-based software, in facilitating inventory checking and recording processes in small and medium-sized enterprises (SMEs). SMEs often face challenges in managing inventory due to limited resources and the absence of sophisticated inventory systems, which may lead to inefficiencies such as overstocking or stock shortages. The integration of a cost-effective and user-friendly tool like Google Sheets offers a practical alternative for improving stock management. Using a case study approach, this research analyzes several SMEs that have implemented Google Sheets as part of their inventory management practices. The findings reveal that Google Sheets significantly eases data entry, enables real-time stock monitoring, and supports collaborative work without additional software licensing costs. Moreover, features like automated formulas and conditional formatting reduce human error in inventory documentation. In conclusion, the study finds that Google Sheets enhances operational efficiency, transparency, and data accuracy in inventory management within SMEs, making it a viable digital solution for improving business performance.